Does More Math in High School Increase the Share of Female STEM Workers? Evidence from a Curriculum Reform - Martin Biewen; Jakob Schwerter (Institute of Labor Economics (IZA), 2019)
This paper studies the consequences of a curriculum reform of the last two years of high school in one of the German federal states on the share of male and female students who complete degrees in STEM subjects and who later work in STEM occupations. The reform had two important aspects: (i) it equalized all students' exposure to math by making advanced math compulsory in the last two years of high school; and (ii) it roughly doubled the instruction time and increased the level of instruction in math and the natural sciences for some 80 percent of students, more so for females than for males. Our results provide some evidence that the reform had positive effects on the share of men completing STEM degrees and later working in STEM occupations but no such effects for women. The positive effects for men appear to be driven by a positive effect for engineering and computer science, which was partly counteracted by a negative effect for math and physics.
Keywords: I23; J16; J24; 330; academic degrees; occupational choice; gender differences